Vatican II as a Constitutional Text of Faith. Issue 1 (22nd May 2014) - Kaplan, Grant
Abstract : This article posits that the hermeneutical approach of Peter Hünermann toward the "text" of the Second Vatican Council possesses the capacity to dissolve disputes that have arisen from a fissure among Catholics about the meaning of the council. At the heart of Hünermann's approach is a bold attempt to read the council's genre in light of "constitutional texts" that have played an important role in founding and reconciling different types of communities in the modern world.